2018
DOI: 10.3803/enm.2018.33.4.473
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Hashimoto Thyroiditis and Clinical Outcomes of Papillary Thyroid Cancer: A Meta-Analysis of Observational Studies

Abstract: BackgroundEpidemiological studies have suggested an association between Hashimoto thyroiditis (HT) and papillary thyroid cancer (PTC) development. Other studies, however, have reported a protective role of HT against PTC progression. Through this updated meta-analysis, we aimed to clarify the effects of HT on the progression of PTC.MethodsWe searched citation databases, including PubMed and Embase, for relevant studies from inception to September 2017. From these studies, we calculated the pooled odds ratios (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 85 publications
9
67
2
4
Order By: Relevance
“…In the meta-analysis conducted by Lee et al involving a group of 10,648 PTC cases, it was shown that AIT was substantially more frequent in patients with PTC, compared to patients with benign tumours [18]. Another meta-analysis of 71 articles (44,034 patients with PTC) also indicated the relationship between PTC and AIT [19]. Moreover, Niedziela et al…”
Section: Casementioning
confidence: 97%
“…In the meta-analysis conducted by Lee et al involving a group of 10,648 PTC cases, it was shown that AIT was substantially more frequent in patients with PTC, compared to patients with benign tumours [18]. Another meta-analysis of 71 articles (44,034 patients with PTC) also indicated the relationship between PTC and AIT [19]. Moreover, Niedziela et al…”
Section: Casementioning
confidence: 97%
“…Some studies suggest that HT is the result of the combined action of genetic susceptibility and environmental factors, but the exact mechanism is still unclear (2). Clinical studies have suggested that HT is associated with the occurrence of papillary thyroid carcinoma (3). One study suggested that in normal thyroid function, HT can also cause neuroinflammation, leading to emotional alterations (4).…”
Section: Introductionmentioning
confidence: 99%
“…The female prevalence observed in most of the thyroid lesions is also dominant in PTC w/ HT where cancer incidence is approximately five times higher in females than in males [15]. A meta-analysis on 71 observational studies reported that PTCs w/ HT are more likely to be multifocal but in general have favorable clinicopathological features including less extrathyroid extension, lymph node and distant metastases, and recurrence than PTCs w/o HT [16].…”
Section: Introductionmentioning
confidence: 99%